(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2006)
Terrorism is defined as unlawful use or threatened use of force or violence by a person or an-organized group against people or property with the intention of intimidating or coercing societies or governments often for ideological or political reason.’ At present terrorism is biggest threat to the world and peaceful Himalayan Kingdom of Nepal is also not an exception to this. In Nepal terrorism is due to Maoist activity that have been referred as terrorist. Due to terrorism, the poor country is suffering from tremendous loss in the field of economic status, education, human rights, tourism and many more sectors. Above 9000 people have been killed due to terrorism till date, which includes security person, Maoists and also civilians. The weapons used were firearm and hence during encounter, chances of survival were very low. The increasing death trends due to terrorism has drawn attention and seem to be an important field for research work.